Administration of Islamic Law in Kadhis’ Court in Zanzibar: A Comparative Study with the Syariah Courts in Malaysia - Hajil, Mohâ€™d Makame (Journal of Malaysian and Comparative Law, 2014)
Protection and application of Muslim Personal Laws (MPL) is one of the fundamental problems presently faced by many Muslims. The practices that regulate social life of Muslims, particularly at State level, do not appear to be fully in accord with Islamic law, may be because the same are politically controlled and statutorily limited. As a consequence, the functioning of the courts elsewhere and that of Kadhi’s Courts in Zanzibar in particular has become both complicated and difficult. The same in a view an attempt is made, hereunder to study and examine the legal framework of administration of MPL in Zanzibar its problems and prospects while juxtaposing it with the practice of the courts in Malaysia without losing the sight of historical developments of the both in this regard. Finally suggestions shall be made as how to strengthen the application of MPL in Zanzibar.